A Strategy for the Economic Optimization of Combined Cycle Gas Turbine Power Plants by Taking Advantage of Useful Thermodynamic Relationships - Godoy, Ezequiel (2010)
Optimal combined cycle gas turbine power plants characterized by minimum specific annual cost values are here determined for wide ranges of market conditions as given by the relative weights of capital investment and operative costs, by means of a nonlinear mathematical programming model. On the other hand, as the technical optimization allows identifying trends in the system behavior and unveiling optimization opportunities, selected functional relationships are obtained as the thermodynamic optimal values of the decision variables are systematically linked to the ratio between the total heat transfer area and the net power production (here named as specific transfer area). A strategy for simplifying the resolution of the rigorous economic optimization problem of power plants is proposed based on the economic optima distinctive characteristics which describe the behavior of the decision variables of the power plant on its optima. Such approach results in a novel mathematical formulation shaped as a system of nonlinear equations and additional constraints that is able to easily provide accurate estimations of the optimal values of the power plant design and operative variables.